2010
DOI: 10.1111/j.1472-8206.2010.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

French summaries of product characteristics: content in relation to therapeutic monitoring of psychotropic drugs

Abstract: The prescription information (summary of product characteristics, SPC) is compiled by the pharmaceutical industry as required by the national regulatory authorities. They vary in their content about the properties of drugs and about the usefulness of therapeutic drug monitoring (TDM) in the blood of patients. Based on a previous study carried out in Germany, the degree of agreement of French SPC for 59 psychotropic drugs with the existing medico-scientific evidence in the area of TDM was examined using a recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Despite TDM's potential, considerable disagreement was found between the information on TDM in official product information and existing medico-scientific evidence. Even for well-studied compounds, such as amitriptyline or clozapine, insufficient information on TDM was found in the product information (Summary of Product Characteristics, SPC) [1020,1221]. For a large number of neuropsychopharmacological drugs, however, the quantification of blood concentrations has become clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…Despite TDM's potential, considerable disagreement was found between the information on TDM in official product information and existing medico-scientific evidence. Even for well-studied compounds, such as amitriptyline or clozapine, insufficient information on TDM was found in the product information (Summary of Product Characteristics, SPC) [1020,1221]. For a large number of neuropsychopharmacological drugs, however, the quantification of blood concentrations has become clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…The information content of SmPCs has been subject to considerable research over the past years [16,19,25,26]. Completeness of information is an essential prerequisite of any medicines information source and this has been pointed out as an issue in SmPCs [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being considered a leading source of information for safety data and evidence-based prescribing decisions [15], SmPCs have been criticized for containing important clinical pharmacology information deficits [16], for being suboptimal sources of information for drug−drug interactions [17], food−drug interactions [18], therapeutic drug monitoring [19], or dose adjustment in renal impairment [20]. In addition, SmPCs have also been criticized for being too verbose, lacking standardization and being heterogeneous [21].…”
Section: Introductionmentioning
confidence: 99%
“…Product information should be supplemented with TDM related data to enhance the therapeutic eff ectiveness of psychoactive drugs. Analyses of German [ 671 ] and French [ 568 ] summaries of product characteristics (SPC) revealed that many SPC do not contain TDM related information in spite of available valid clinical-scientifi c evidence. Another need for research is to study cost-eff ectiveness of TDM when the method is used in an appropriate way.…”
Section: Conclusion and Perspectives ▼mentioning
confidence: 99%